2022
DOI: 10.20517/cdr.2021.109
|View full text |Cite
|
Sign up to set email alerts
|

Tousled-like kinase 1: a novel factor with multifaceted role in mCRPC progression and development of therapy resistance

Abstract: Standard treatment for advanced Prostate Cancer (PCa) consists of androgen deprivation therapy (ADT), but ultimately fails, resulting in the incurable phase of the disease: metastatic castration-resistant prostate cancer (mCRPC). Targeting PCa cells before their progression to mCRPC would greatly improve the outcome, if strategies could be devised selectively targeting androgen receptor (AR)-dependent and/or independent compensatory pathways which promote mCRPC development. Combination therapy by targeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Upon development of castration-resistance, prostate cancer growth is, at least in part, achieved through mTOR activation and consequent upregulation of TLK1B [ 121 ]. The molecular mechanism was explored by Khalil and Benedetti who found that ADT inhibits the AR signaling pathway by blocking the nuclear relocation of AR, resulting in downregulation of the androgen-responsive gene FKBP5 , which controls intracellular glucocorticoid signaling and holds an important role in stress response modulation [ 121 ].…”
Section: Interplay Of Ddr/hippo/notch Pathways In Prostate Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Upon development of castration-resistance, prostate cancer growth is, at least in part, achieved through mTOR activation and consequent upregulation of TLK1B [ 121 ]. The molecular mechanism was explored by Khalil and Benedetti who found that ADT inhibits the AR signaling pathway by blocking the nuclear relocation of AR, resulting in downregulation of the androgen-responsive gene FKBP5 , which controls intracellular glucocorticoid signaling and holds an important role in stress response modulation [ 121 ].…”
Section: Interplay Of Ddr/hippo/notch Pathways In Prostate Cancermentioning
confidence: 99%
“…Upon development of castration-resistance, prostate cancer growth is, at least in part, achieved through mTOR activation and consequent upregulation of TLK1B [ 121 ]. The molecular mechanism was explored by Khalil and Benedetti who found that ADT inhibits the AR signaling pathway by blocking the nuclear relocation of AR, resulting in downregulation of the androgen-responsive gene FKBP5 , which controls intracellular glucocorticoid signaling and holds an important role in stress response modulation [ 121 ]. This, subsequently, leads to AKT and mTORC1 activation, which results in activation of eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1) and upregulation of the master eukaryotic translation switch eIF4E [ 121 ], which, in turn, initiates TLK1B translation.…”
Section: Interplay Of Ddr/hippo/notch Pathways In Prostate Cancermentioning
confidence: 99%
See 3 more Smart Citations